Assessing ESL University Students’ Metacognitive Online Reading Strategies - Ruhil Amal, Azmuddin; Nurul Nadia, Muhammad; Uthayakumaran, Arulselvi; Hamizah, Zahari (2023)
Extracting information through online reading has become second nature to ESL students in higher institutions. Although online reading is indispensable among ESL university students, they lack the ability to read effectively. The present study examines students' metacognitive online reading strategies and how those strategies reflect understanding of scientific online reading materials for academic purposes. This was conducted through an online survey and semi-structured interviews. Data was collected among 55 university students enrolled in various Science and Technology courses. Out of the same sample, ten students were selected to participate in the interviews. Data were analyzed using descriptive statistics and thematic analysis with the use of SPSS and NVivo respectively. Thematic analysis was validated using inter-rater reliability analysis through Cohen Kappa analysis that yielded substantial results, indicating that the findings were reliable. Although the findings from the survey revealed that problem-solving strategies were used mainly by students, semi-structured interviews found contradicting results where support reading strategies were believed to reflect understanding by students. Implications that can be drawn are two folds. Students are motivated to use metacognitive online reading strategies depending on the type of texts; two, the need to use different reading strategies to elicit purposeful information based on the subject matter.